Written Discourse Performance of Senior High School Students: Designing Genre-Based Instructional Material - REFORSADO, Mariz; RAYMUNDO, Jennelyn Lacar (Research and Innovation in Applied Linguistics, 2025)
This study investigates the written discourse performance of Grade 11 senior high school students with a focus on designing genre-based instructional material. The research encompasses a detailed examination of demographic profiles, reading material preferences, and academic strands to provide comprehensive understanding of students' backgrounds. Methodologically, quantitative approach was employed, involving writing a position paper collection from 258 respondents across various schools. Data analysis included descriptive statistics and inferential tests to identify the level of written discourse performance and significant factors influencing written discourse competence. Findings reveal significant challenges in students' written discourse performance, particularly in organization and transitional signals appropriacy. A notable proportion of students demonstrated deficiencies in these areas, highlighting the need for targeted interventions in writing instruction. The study also underscores the impact of students' reading habits on their writing proficiency, emphasizing the beneficial role of diverse reading materials such as journals and literary works. Gender-based analysis indicates an equitable distribution of writing abilities between male and female students, suggesting inclusive instructional strategies effectively support learners. The study concludes by proposing genre-based instructional materials tailored to students' reading preferences and academic contexts. These materials aim to address identified deficiencies in written discourse performance and enhance overall language proficiency.